2014
DOI: 10.1021/ma5019022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chiroptical Properties of Helical Polyallenes Bearing Chiral Amide Pendants

Abstract: Two allene derivatives, L-and D-N-(1-(octylamino)-1-oxopropan-2-yl)-4-(propa-1,2-dien-1-yloxy)-benzamide (L-1 and D-1), bearing chiral amide pendants were designed and synthesized. Living polymerizations of L-1 and D-1 with allylnickel complex as a catalyst afforded poly-L-1 m and poly-D-1 m with controlled molecular weights and narrow molecular weight distributions. These polymers were found to possess a stable helical conformation with a preferred handedness in aprotic solvents on the basis of their circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 75 publications
0
55
0
Order By: Relevance
“…When the spectra were recorded for the mixture of P15 and guest AD0 with increased enantiomeric excess ( ee ), the CD signals were nonlinearly enhanced with the increase of the ee of the guest and 70% ee of the guest led to the maximum CD intensity. This result indicated that the induction of the helicity bias of the helical backbone obeyed the majority role . The induction of the twist‐sense bias of P15 by another seven chiral aspartate derivatives AD1 ‐ 7 was also studied.…”
Section: Polymeric Aromatic Amide‐based Tubular Helicesmentioning
confidence: 85%
“…When the spectra were recorded for the mixture of P15 and guest AD0 with increased enantiomeric excess ( ee ), the CD signals were nonlinearly enhanced with the increase of the ee of the guest and 70% ee of the guest led to the maximum CD intensity. This result indicated that the induction of the helicity bias of the helical backbone obeyed the majority role . The induction of the twist‐sense bias of P15 by another seven chiral aspartate derivatives AD1 ‐ 7 was also studied.…”
Section: Polymeric Aromatic Amide‐based Tubular Helicesmentioning
confidence: 85%
“…[ 52 ] In sharp contrast to PBLG 35 -PPI(L) 50 , the PBLG 38 -PPI(D) 52 block copolymer showed a strong negative Cotton effect (a mirror image of that of PBLG 35 -PPI(L) 50 ) in the 260-475 nm region, which indicated that the PBLG possessed the same apha-helix as that in PBLG 35 . TEM images obtained for (b) PBLG 36 -PPI(L-co -D) 50 , (c) PBLG 35 -PPI(L) 50 , and (d) PBLG 36 -PPI(L-co -D) 50 copolymers dried from TCE. copolymers, while the PPI(D) segment behaved as an opposite-handed helical conformation to that of the PPI(L) segment in TCE.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that no concentration-induced copolymer aggregation occurred in the current concentration range. To examine in more depth the effect of the chirality of L-PI and D-PI monomers on the helical sense of the resulting copolymers, a contrast experiment was performed on the synthesized PBLG 36 -PPI(L-co -D) 50 Table 1 (run 5). The SEC trace is shown in Figure S6 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations